Investigating Students' Readiness for Implementing Small Private Online Courses (SPOC) in Trigonometry within Indonesian High Schools - Yusnita Rahayu; Yayat Ruhiat; Cucu Atikah (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study examined the readiness of Indonesian high school students to engage in blended learning using a Small Private Online Course (SPOC) for trigonometry instruction and identified factors that support or hinder this readiness. Using a quantitative descriptive design, data were collected from 58 Grade XI students at SMA Negeri 5 Kota Serang. A validated questionnaire measured six readiness dimensions: cognitive understanding, learning motivation, digital literacy, access to technology, learning environment, and interaction skills. The instrument demonstrated strong reliability (Cronbach’s Alpha = 0.875). Results indicated that 81% of students were categorized as “very ready,” reflecting high preparedness, especially in digital access and cognitive understanding. Nevertheless, several constraints emerged, including decreased motivation, less supportive learning environments, and limited self-regulation. These findings suggest that SPOC-based trigonometry learning can be implemented immediately or in the near term, provided schools strengthen support mechanisms such as digital orientation, motivational scaffolding, and structured learner assistance. The study contributes practical evidence to inform classroom implementation and broader mathematics education policy in Indonesia.